Comparative analysis of pregnancy complications: primigravida versus multigravida - Amin, Fiza; Tali, Tavseef A.; Ara, Rifat; Amin, Huda (International Journal of Research in Medical Sciences, 2023)
Background: The study aimed to compare the outcome of pregnancies in a primigravida with multigravida. Methods: This retrospective study was conducted in Skims Medical College, Srinagar between May 2017 to December 2018 in which hospital records of 135 patients who delivered during the study period were analysed. Results: Majority of primigravida mothers falls in 21-30 years of age group 34 (54.83%), whereas 46 (65.75%) of multigravida were in 31-40 years. Incidence rate of gestational hypertension, gestational diabetes, post-partum haemorrhage, placenta previa, oligohydramnios, pre term labour, intrauterine growth retardation (IUGR) was higher in primigravida when compared to multigravida. Conclusions: Despite the fact that primigravida had the majority of the issues, both groups experienced considerable issues. Therefore, in order to promote maternal health, women should get information about appropriate medical care as well as counselling. It will help to prevent unfavourable pregnancy outcomes.